Matching physicians’ treatment recommendations to patients’ treatment preferences is associated with improvement in treatment satisfaction - Umar, Nasir; Schaarschmidt, Marthe-Lisa; Schmieder, Astrid; Ludwig-Peitsch, Wiebke; Terris, Darcey D. (Journal of the European Academy of Dermatology and Venereology, 2013)
Background: Dissatisfaction with treatment is common among those with psoriasis. While incorporating patients’ preferences into the process of treatment decision-making may improve satisfaction, this relationship has not been clearly established. Objective: To assess the extent to which matching physicians’ treatment recommendations to patients’ treatment preferences is associated with improvement in treatment satisfaction in patients with moderate-to-severe psoriasis. Methods: This prospective cohort study design examined change from baseline to 3-month follow-up in four subscales of an established measure of treatment satisfaction. Separate multivariate regression models investigated the association of change in these subscale scores with an index measuring the match between physicians’ treatment recommendations and patients’ treatment preferences at the initial study visit. Results: A closer match between physicians’ recommendations and patients’ preferences was associated with greater improvement in treatment satisfaction over time in each of the four subscales: effectiveness (β = 0.53, P < 0.001), side-effects (β = 0.25, P = 0.009), convenience (β = 0.78, P < 0.001) and global satisfaction (β = 0.49, P < 0.001). Adjusted models explained as much as 76% of the variation in change in treatment satisfaction subscales over 3 months. Conclusions: Further efforts to incorporate patients’ preferences in treatment decision-making appear justified given the strength of independent associations between preference matching and improved treatment satisfaction and the extent to which our models explained variation in this relationship. An approach based on preference matching shows promise for increasing satisfaction in the management of other chronic diseases.